PEMANFAATAN TEPUNG KACANG HIJAU DAN TEPUNG IKAN DALAM UPAYA PENGEMBANGAN PRODUK MAKANAN FORMULA BALITA BERBASIS PANGAN LOKAL BERAS MERAH DAN PISANG - Dalung, Godeliva; Picauly, Intje; Jutomo, Lewi (Pergizi Pangan DPD NTT, 2010)
Food formula could is easily reserved as usual food for children under five years old. Giving additional food to preschool children can increase body weight and hemoglobin content to prevent the incidence of protein and energy malnutrition (PEM). The purpose of the research is to know the impact of food formula product using mug-bean and fish flour with local red rice and banana as basic food. Factorial experimental design with two-time replications and Randomized Block Design (RBD) as basic design were used in the research. Protein content was analyzed using Kjeldahl methods, and carbohydrate content was analyzed using Shaffer-Somogyi II methods, while fat content was analyzed using extract ether. The result of the research showed that there was a significant difference (P<0.05) and higher protein content on additional 50 grams of mug-bean and fish flour separately compared with an additional 0 and 25 grams of mug-bean and fish flour respectively. While carbohydrate content analysis for additional mug-bean on food formula showed that the additional 50 grams of mug-bean and fish flour separately has a significant difference (P<0.05) and lower carbohydrate content compared with additional 0 and 25 gram of mug-bean and fish flour respectively.